Conformational dynamics of amyloid-β (16–22) peptide in aqueous ionic liquids. Issue 55 (8th September 2020) - Dasari, Sathish; Mallik, Bhabani S.
Abstract : Molecular dynamics simulations of amyloid-β (16–22) peptide dimer at two different experimentally studied concentrations of hydrated ethylammonium mesylate, ethylammonium nitrate, and triethylammonium mesylate were carried out employing an umbrella sampling method. Abstract : Molecular dynamics simulations of amyloid-β (16–22) peptide dimer in water as well as at two different experimentally studied concentrations of hydrated ionic liquids (ILs), ethylammonium mesylate (EAM), ethylammonium nitrate (EAN), and triethylammonium mesylate (TEAM), were carried out employing an umbrella sampling method. We used the average Ψ angle of the peptide backbone as the reaction coordinate to observe the conformational changes of a peptide dimer. Secondary structural element values were calculated for the peptide dimer along the reaction coordinate to see the transition of the peptide dimer between β-sheet and α-helix conformations. We observe the β-sheet conformation as the global minimum on the free energy surfaces in both EAM and EAN ILs at both the concentrations and at a low concentration of TEAM. However, we observe α-helix conformation as the global minimum at a high concentration of TEAM. Our results are in good correlation with the experimental findings. We calculated the average number of intramolecular and intermolecular hydrogen bonds of α-helix and β-sheet conformations in all solutions, and they are in correlation with the secondary structure element values. To understand the peptide–IL interactions, atom–atom radial distribution functions of cation, anion, and water around amide oxygen and hydrogen atoms were calculated. The solvent-accessible surface area of the peptide dimer was calculated to understand the exposure of the peptide towards the solvent during conformational changes. Finally, van der Waals (vdW) and Coulomb interaction energies were calculated between peptide–cation, peptide–anion, and peptide–water to understand the stability of conformations in different concentrations. We find that the TEA cation has more vdW interaction energy compared to Coulomb interaction energy with peptide in 70% (w/w) TEAM, which mimics a membrane-like environment to induce α-helix conformation rather than β-sheet conformation.